KONTRAK PSIKOLOGIS DAN KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN BAGIAN PRODUKSI PT. ROYAL KORINDAH PURBALINGGA - Nerisha Nainaya; Retno Dwiyanti; Ugung Dwi Ario Wibowo; Fatin Rohmah Nur Wahidah (Program Studi S1 Psikologi, 2022)
An organization or workplace certainly needs employees who are committed to making it easier to achieve their goals. The purpose of this study was to determine the effect of psychological contracts and organizational justice on organizational commitment to employees of the production division of PT. Royal Koridah Purbalingga. The research method used is a quantitative approach, with the number used as many as 250 with a sampling technique using Simple Random Sampling or random sampling in a population according to a predetermined number. Simple random sampling is included in probability sampling, which is a sampling technique that provides equal opportunities for each individual (member) of the population. Data were collected using a measuring instrument that has been adapted from the Organizational Commitment Questionnaire (OCQ) (0.856), Psychological Contract Inventory (PCI) (0.887) and Justice Scale (0.914) measurement tools. The data analysis technique used multiple linear regression analysis techniques. The results of the analysis show that there is a significant and positive effect on psychological contract on organizational commitment by 8.8% with (Fcount = 22.57; p<0.05) and fairness to organizational commitment of 6.6% with a value (Fcount = 17.465; p<0.05), in addition it was found that psychological contracts had Tcount = 3,950 and organizational justice had Tcount = 3,265; p<0.05) and Rsquare of 0.121 which shows that psychological contract and organizational justice contribute 12.1% effectively to organizational commitment. so that the increase in psychological contracts and organizational justice can increase organizational commitment to employees of the production division of PT. Royal Korindah Purbalingga.